Large-scale assessment of commensalistic-mutualistic associations between African birds and herbivorous mammals using internet photos - Mikula, Peter; Hadrava, Jiří; Albrecht, Tomáš; Tryjanowski, Piotr (PeerJ, 2018)
Birds sitting or feeding on live large African herbivorous mammals are a visible, yet quite neglected, type of commensalistic-mutualistic association. Here, we investigate general patterns in such relationships at large spatial and taxonomic scales. To obtain large-scale data, an extensive internet-based search for photos was carried out on Google Images. To characterize patterns of the structural organization of commensalistic-mutualistic associations between African birds and herbivorous mammals, we used a network analysis approach. We then employed phylogenetically-informed comparative analysis to explore whether features of bird visitation of mammals, i.e., their mean number, mass and species richness per mammal species, are shaped by a combination of host mammal (body mass and herd size) and environmental (habitat openness) characteristics. We found that the association web structure was only weakly nested for commensalistic as well as for mutualistic birds (oxpeckers Buphagus spp.) and African mammals. Moreover, except for oxpeckers, nestedness did not differ significantly from a null model indicating that birds do not prefer mammal species which are visited by a large number of bird species. In oxpeckers, however, a nested structure suggests a non-random assignment of birds to their mammal hosts. We also identified some new or rare associations between birds and mammals, but we failed to find several previously described associations. Furthermore, we found that mammal body mass positively influenced the number and mass of birds observed sitting on them in the full set of species (i.e., taking oxpeckers together with other bird species). We also found a positive correlation between mammal body mass and mass of non-oxpecker species as well as oxpeckers. Mammal herd size was associated with a higher mass of birds in the full set of species as well as in non-oxpecker species, and mammal species living in larger herds also attracted more bird species in the full set of species. Habitat openness influenced the mass of birds sitting on mammals as well as the number of species recorded sitting on mammals in the full set of species. In non-oxpecker species habitat openness was correlated with the bird number, mass and species richness. Our results provide evidence that patterns of bird-mammal associations can be linked to mammal and environmental characteristics and highlight the potential role of information technologies and new media in further studies of ecology and evolution. However, further study is needed to get a proper insight into the biological and methodological processes underlying the observed patterns.
Keywords: Oxpeckers; Herbivores; Commensalism; Web network analyses; Mutualism; Bird–mammal interactions